Recent Progress of Photocatalytic Fenton-Like Process for Environmental Remediation - Dong, Chencheng; Xing, Mingyang; Zhang, Jinlong (Frontiers in Environmental Chemistry, 2020)
Over the past few decades, Fenton process has been widely studied in environmental remediation. Due to the low efficiency of iron ions recycling, the Fenton efficiency has been seriously impeded for practical application. On this condition, with combination of photocatalysts, it is expected to fully use photo-generated electrons, thus enhancing the photo-Fenton efficiency. This synergistic methodology has assisted many researchers to remove various categories of organic pollutants in discharged wastewater or achieve gas conversion. This comprehensive review describes some significant advances with respect to presentative semiconductors (e.g. TiO2, g-C3N4, graphene, BiVO4, ZnFeO4 and BiFeO3, etc.) including their preparation methods, characterization and applications in environmental remediation (e.g., organic removal, bacteria disinfection, membrane separation, and gas conversion). The mechanism is preferentially discussed. Possibly future development and its correlated potential challenges are specifically proposed and discussed in this review.